Authoring professional identity: Pre-service teachers and ways of knowing - Hill, S. Laurie (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2022)
Education programs increasingly emphasize the development of strong core beliefs and values to support professional judgment for pre-service teacher practice. The ability to critically integrate multiple perspectives is an expected foundation for the pedagogical decisions and professional responsibilities preservice teachers carry out. This article details research undertaken to investigate pre-service teachers’ ways of knowing as they progress through a Bachelor of Education program. Findings from semi-structured interviews are discussed in terms of supporting pre-service teacher intellectual development in teacher education programs so that a professional teacher identity is encouraged.